Assessment of Health Care Seeking Behavior among House Hold Heads in Dale Woreda, Sidama Zone, Southern Ethiopia, Ethiopia (Global Journal of Medical Research, 2018)
Abstract not found
Keywords: appropriate health seeking behavior; inappropriate health-seeking behavior; keble; urban; rural